Prodigal Son - Steel, Danielle (New York : Dell, 2016)
"In a matter of days, Peter McDowell loses everything he has worked so hard for--his wealth, his property, his livelihood. Stripped of everything, he has only one place to retreat: a lakeside cottage he inherited from his parents, who left most of their modest estate to Peters twin. With no other choice, the prodigal son goes home. A beloved small-town doctor, a devoted family man, and a pillar of his community, Michael McDowell serves others without regard to personal gain. Only Peter knows how Michael manipulated their parents when the boys were young, ultimately driving Peter away. At first, he dreads seeing Michael again. But, to his surprise, their reunion is tender and real. Only later, as Peter mulls over his mothers journals, does the truth begin to emerge, as realization and panic begin to set in. In a race for time, Peter throws caution to the winds to find the truth."-- Publishers description.
Keywords: Twin brothers -- Fiction; Family secrets -- Fiction; Reconciliation -- Fiction; Sibling rivalry -- Fiction; Fiction